PENINGKATAN PENGETAHUAN TENTANG OBESITAS DENGAN APLIKASI “BANG ABE” YANG BERBASIS WEB PADA ANAK REMAJA - Alpari Nopindra; Abdan Saquro; Ekawira Armizan (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2022)
Background: Obesity/overweight has become a global pandemic throughout the world and is declared by the World Health Organization (WHO) as the biggest chronic health problem. Obesity or commonly known as overweight is a problem that is quite worrying among adolescents. The problem of obesity/overweight in children and adolescents can increase the incidence of type 2 diabetes mellitus (DM). This study aims to develop a WEB-based “Bang ABE” application to increase knowledge about obesity in adolescents. Method: This research method uses a research and development approach which is carried out by designing and developing applications as well as field tests on students of SMAN 6 Jambi City about the dangers of obesity in adolescents. Results: Based on the results of the study it was found that there was an increase in knowledge about obesity prevention (p-value <0.005) Conclusion: There has been an increase in knowledge about the importance of maintaining health, especially obesity using a web-based application to prevent obesity in adolescents at SMAN 6 Jambi City with an attractive appearance and easy to use (user friendly).